Is tolerance good or bad for growth? - Niclas Berggren; Mikael Elinder (Uppsala University, Department of Economics, 2010)
We investigate to what extent tolerance, as measured by attitudes toward different types of neighbors, affects economic growth. Data from the World Values Survey enable us to investigate tolerance-growth relationships for 54 countries. We provide estimates based on cross-sectional as well as panel-data regressions. In addition we test for robustness with respect to model specification and sample composition. Unlike previous studies, by Richard Florida and others, we find that tolerance toward homosexuals is negatively related to growth. For tolerance toward people of a different race, we do not find robust results, but the sign of the estimated coefficients is positive, suggesting that inclusion of people irrespective of race makes good use of productive capacity. We propose mechanisms to explain these divergent findings, which clarify why different kinds of tolerance may be of different economic importance.
urn:nbn:se:uu:diva-129537
Keywords: O40; Z13; 330; Tolerance; Growth; Diversity; Human Capital; Creativity; Innovation; Soziales Verhalten; Soziale Beziehungen; Wirtschaftswachstum; Humankapital; Kreativität; Innovation; Welt